ENGLISH SUPRASEGMENTAL FEATURES IN SPEECH SOUND ERRORS PRODUCED BY EFL ELEMNETARY STUDENTS - Wardani Dwi Wihastyanang (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2020)
This study concerns on a phonological analysis on EFL Students’ speech sound errors. The writer identified kinds of waveforms pronunciation made by EFL Students of SDN Pesanggrahan in vowels, diphthongs, and consonants, the differences of waveforms pronunciation between EFL Students’ and British English and Emerican English based on CALD to find kinds of speech sound errors. In the process of data collection, the writer used descriptive qualitative. The subject of the research is the 30 EFL students of SDN Pesanggrahan Jombang in academic year 2009-2010. The writer recorded the EFL Students speech sound by using Adobe Audition then analysed it by using Speech Analyzer. After analyzing all the data, the writer then found there are some errors. Majority EFL students make speech sound errors for vowel and diphthongs production in the additions, distortion and substitutions category. The result for consonants speech sound production, majority EFL students make speech sound errors in the distortion and addition category.There are several categories that are the EFL students’ reasons in producing speech sound error. These results can generally namely, (1) English-speaking habit, (2) learning method, (3) Students' interest in learning English, (4) the role of teacher of English in school, (5) The role of parents in accompanying the student to learn at home. Based on the result most of the EFL students only speak English in the school. There are several categories that are the reasons of EFL students. These results can generally be divided into two categories, namely, (1) Internal factors, and (2) External Factors. The results of interview and observation, 99% of 30 EFL students claim to have no problem dealing with their organ of speech. There is only one EFL student who has sound production problem in which he cannot produce letter r /r/ correctly. 40% of 30 EFL students claim that they feel groggy and lack of self-confidence at the time of recording so that there are several errors in pronouncing several words, whereas 20% of EFL students feel that they do not know how to read or pronounce certain words, for those words are new vocabulary for them. 40% other EFL students do not declare themselves as having psychic problems experienced by other students.